The perks of being a wallflower - Chbosky, Stephen (New York : Pocket Books, 1999)
A coming of age novel about Charlie, a freshman in high school who is a wallflower, shy and introspective, and very intelligent. He deals with the usual teen problems, but also with the suicide of his best friend.
720
Accelerated Reader AR
Keywords: Coming of age -- Juvenile fiction; High school students -- Juvenile fiction; Epistolary fiction; Bildungsromans